2011
DOI: 10.1158/1078-0432.ccr-11-0063
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Inflammatory Myofibroblastic Tumor Expressing a Novel Fusion, PPFIBP1–ALK: Reappraisal of Anti-ALK Immunohistochemistry as a Tool for Novel ALK Fusion Identification

Abstract: Purpose: The anaplastic lymphoma kinase (ALK) inhibitor crizotinib has been used in patients with lung cancer or inflammatory myofibroblastic tumor (IMT), both types harboring ALK fusions. However, detection of some ALK fusions is problematic with conventional anti-ALK immunohistochemistry because of their low expression. By using sensitive immunohistochemistry, therefore, we reassessed "ALK-negative" IMT cases defined with conventional immunohistochemistry (approximately 50% of all examined cases).Experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 45 publications
(55 reference statements)
2
76
0
Order By: Relevance
“…Recent reports have suggested that ALK1/ avidin-biotin method may result in suboptimal concordance between immunoreactivity and genomic status. [29][30][31] The differential ALK staining in rhabdomyosarcoma may carry diagnostic value. Subtyping rhabdomyosarcoma can be challenging, particularly when alveolar tumor shows a solid pattern and embryonal tumor shows dense cellularity without an apparent myxoid matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that ALK1/ avidin-biotin method may result in suboptimal concordance between immunoreactivity and genomic status. [29][30][31] The differential ALK staining in rhabdomyosarcoma may carry diagnostic value. Subtyping rhabdomyosarcoma can be challenging, particularly when alveolar tumor shows a solid pattern and embryonal tumor shows dense cellularity without an apparent myxoid matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of IMTs harbor an ALK fusion gene, which is normally found in anaplastic large-cell lymphoma, non-small-cell lung cancer (NSCLC) and large B-cell lymphoma, as well as IMT (6). Pulmonary IMTs harboring TPM3-ALK or PPFIBP1-ALK have been reported previously (4,5). EML4-ALK is known to be an abnormality of NSCLC (7), with a prevalence of 1 -5% (8 -10).…”
Section: Discussionmentioning
confidence: 99%
“…However, anaplastic lymphoma kinase (ALK) fusion gene abnormalities in IMTs are a specific finding that differentiates these tumors from other tumors. Pulmonary IMTs harboring tropomyosin3-anaplastic lymphoma kinase (TPM3-ALK) or protein tyrosine phosphatase receptor-type F polypeptide-interacting proteinbinding protein 1-anaplastic lymphoma kinase (PPFIBPI-ALK) have been reported previously (4,5), while echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion has been considered largely specific to lung adenocarcinoma and an IMT harboring EML4-ALK fusion gene has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…TPM4 as the ALK fusion partner has not been described previously in pulmonary tumor. Six TPM4-ALK fusion cases have been reported in abdomen, mesentery, prostate, urinary bladder and hematologic malignant disease (10,11). These reported TPM4-ALK patients were relatively young at 1 to 25 years of age.…”
Section: A B C Dmentioning
confidence: 99%